Measuring nominal and real convergence of selected CEE countries by the Taylor rule - Tobias Böing; Georg Stadtmann; Meerim Sydykova (International Journal of Management and Economics, 2016)
We propose using a simple Taylor rule to evaluate business cycle convergence of the Czech Republic, Hungary, and Poland with the Eurozone. Our findings indicate an ongoing convergence of those CEE countries to the Eurozone, but with instabilities and heterogeneity between the countries. Especially Poland has shown a high degree of convergence in recent years. But there are still relevant differences in Taylor rates of each country to the Eurozone of about two percentage points.
Keywords: E52; E58; F15; 650; CEE; monetary policy; currency union; convergence; Taylor rule